Frederick Joseph Libby papers - Libby, Frederick J. (Frederick Joseph), 1874-1970.; Libby, Abial
Correspondence, diaries, articles, essays, sermons, notes, financial papers, printed material, broadsides, ship's papers, maps, and other papers relating chiefly to Libby's life and work as a peace activist and executive secretary of the National Council for Prevention of War (1921-1970). Includes material pertaining to his years as pastor of the Union Congregational Church, Magnolia, Mass. (1905-1911), and as a faculty member at Phillips Exeter Academy, Exeter, N.H. (1912-1920), to his travels in East Asia, Europe, the Middle East, and the South, and to war relief service with the American Friends Service Committee (1918-1920). Topics include Bible study, birth control, child labor, military preparedness, pacifism, and prostitution. Also includes a diary kept by Libby's father Abial Libby as a surgeon with Union forces during the Peninsular Campaign in Virginia in 1862. Correspondents include Markham W. Stackpole, pacifists Harold Studley Gray and Leyton Richards, and members of the Libby family.
Library of Congress Geography and Map Division.
Library of Congress Prints and Photographs Division.
Clergyman and pacifist; died 1970.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Gray, Harold Studley, -- 1894- -- Correspondence; Richards, Leyton, -- 1879-1948 -- Correspondence; Stackpole, Markham W. -- Correspondence; Libby family -- Correspondence; American Friends Service Committee; National Council for Prevention of War (U.S.); Phillips Exeter Academy; Union Congregational Church (Magnolia, Mass.); Bible -- Study and teaching; Birth control; Child labor; Military readiness; Pacifism; Pacifists; Peace -- Societies, etc; Peninsular Campaign, 1862.; Private schools -- New Hampshire -- Exeter; Prostitution; East Asia -- Description and travel; Europe -- Description and travel; Middle East -- Description and travel; Southern States -- Description and travel; United States -- History -- Civil War, 1861-1865 -- Campaigns; Virginia -- History -- Civil War, 1861-1865 -- Campaigns; Clergy; Pacifists